Measurement of Fruit and Vegetable Intake Using Skin Carotenoid Measures Among Individuals Receiving Aid from Food Pantries (P04-087-19). (13th June 2019) - Valentine, Heather; Mount, Rebecca; Wolff, Kathryn; Ousley, Lisa; Worm, Emily; Lee, Jaehoon; Sullivan, Debra; Gibson, Cheryl
Abstract: Objectives: The purpose of this study was to understand food security and fruit/vegetable consumption among individuals receiving aid from food pantries and other food assistance agencies. Methods: Across the US, 12.9% of people are affected by food insecurity 1 and 5.5% of households report obtaining food from a food pantry 2 . Similarly, food insecurity affects 12.9% of the population in Kansas and 14.7% in Missouri 1 . After the Harvest is a nonprofit organization that helps address food insecurity by rescuing fruits and vegetables from going to waste and donating them to agencies that serve hungry people in the Kansas City metropolitan area. As part of a larger evaluation of the After the Harvest program, intercept surveys with individuals receiving aid from food pantries and other food assistance agencies were conducted at selected locations in the Kansas City area. In each survey, a demographic questionnaire and a Dietary Screener Questionnaire were administered. Food insecurity was screened using two items derived from the USDA's Food Security Survey Module. Additionally, skin carotenoids were measured using the Veggie Meter™ as a biomarker of fruit and vegetable intake. Results: A total of 57 food agency clients participated in the study. About 67% of the clients indicated that within the past 12 months, they had worried about their food running out before having money to buy more. Additionally, 74% reported that the food they bought didn't last and they didn't have money to buy more. On average, the food agency clients reported eating 1 cup of fruit per day and 1.4 cups of vegetables per day, which fell far below recommendations set by the Dietary Guidelines for Americans. Similarly, they had a Veggie Meter™ score of 175 ± 77, indicating a very low level of fruit and vegetable intake. Conclusions: Food agency clients were food insecure and had very low fruit and vegetable intakes. Efforts to increase the amount of fresh fruit and vegetable donations at food assistance agencies may represent an opportunity to improve the diets among clientele. Funding Sources: The Hall Family Foundation.